2020
DOI: 10.3390/ijms21082870
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis by Day 16 Bovine Conceptuses during the Time of Maternal Recognition of Pregnancy

Abstract: Interferon Tau (IFNT), the conceptus-derived pregnancy recognition signal in cattle, significantly modifies the transcriptome of the endometrium. However, the endometrium also responds to IFNT-independent conceptus-derived products. The aim of this study was to determine what proteins are produced by the bovine conceptus that may facilitate the pregnancy recognition process in cattle. We analysed by mass spectrometry the proteins present in conceptus-conditioned media (CCM) after 6 h culture of Day 16 bovine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…da Silveira et al (2017) observed that when the culture medium of somatic cell nuclear transfer is supplemented with EVs from the uterus, bovine blastocyst rates and interferon tau (IFNT) expression are improved (Qiao et al, 2018). Protein cargoes in EVs have also been studied, and it seems that maternal-embryonic communication independent of IFNT could be regulated by protein cargoes of EVs secreted by conceptus (Malo Estepa et al, 2020). Ninety-seven proteins are expressed exclusively in EVs of the oviduct in vivo versus in vitro, related to spermatozoa union, fertilization, and embryo development (Almiñana et al, 2017).…”
Section: Embryo Development and Uterine Interactionmentioning
confidence: 99%
“…da Silveira et al (2017) observed that when the culture medium of somatic cell nuclear transfer is supplemented with EVs from the uterus, bovine blastocyst rates and interferon tau (IFNT) expression are improved (Qiao et al, 2018). Protein cargoes in EVs have also been studied, and it seems that maternal-embryonic communication independent of IFNT could be regulated by protein cargoes of EVs secreted by conceptus (Malo Estepa et al, 2020). Ninety-seven proteins are expressed exclusively in EVs of the oviduct in vivo versus in vitro, related to spermatozoa union, fertilization, and embryo development (Almiñana et al, 2017).…”
Section: Embryo Development and Uterine Interactionmentioning
confidence: 99%
“…Despite that the major pregnancy recognition signal in ruminants, interferon-tau, has been discovered long time ago [ 26 ], more and more studies are showing that other embryonic molecules are involved in the establishment of pregnancy, pointing out the high complexity of these interactions. In this line, Malo Estepa et al, examined the protein synthesis by day 16 conceptuses corresponding to the phase of maternal recognition of pregnancy [ 27 ], identifying a set of conceptus-derived proteins that may be involved in EV-mediated IFNT-independent embryo–maternal communication during pregnancy recognition in cattle.…”
Section: The Embryomentioning
confidence: 99%
“…Fine-tuned and reciprocal crosstalk involves secreted ligands, their interacting receptors, and coupled pathways between the conceptus and endometrium. Until now, most research has focused on either the conceptus (23)(24)(25)(26) or the endometrium (20,21,(27)(28)(29) in isolation, the lack of integrated analysis between the paired conceptus and endometrium has made it challenging to advance our understanding of the pathways and functions that govern conceptus-endometrium crosstalk during implantation. More recently, disrupted crosstalk following somatic cell nuclear transfer (SCNT) (30), IVF (31), and fertilityclassi ed animals (32) have been pro led, and revealed important clues to failed implantation and pathological pregnancy induced by impaired conceptus-endometrium crosstalk.…”
Section: Introductionmentioning
confidence: 99%